Southwest Historical Series Pike's Peak Gold Rush Guidebooks of 1859 Volume 9 - 20160731 frey50; Parsons, William B.; Hafen, LeRoy R. (Arthur H. Clark Company Glendale, CA, 1943)
History of the Pike's Peak gold rush in 1859.
Keywords: Pike's Peak -- Colorado -- History; Gold -- Colorado -- History; West (U.S.) -- Guidebooks